THE MODERN INNOVATIVE TECHNOLOGIES IN TEACHING FOREIGN LANGUAGES - Teshaboyeva, Nafisa (Журнал иностранных языков и лингвистики, 2023)
The article deals with investigating the significance of using modern innovative technologies while teaching a foreign language. Since learners should be able to learn English fluently and appropriately they should develop their reading, listening, writing and speaking skills. Namely, the aim of teaching a foreign language is a communicative activity of learners. Hence, the appropriate use of modern innovative technologies, modern tools such as news programs, podcasts, magazines and web based technologies as well as cooperative learning and project methodology, permit us to solve this problem.